In Vivo and in vitro antitumor activity of tomatine in hepatocellular carcinoma - Echeverría, Cesar; Martin, Aldo; Simon, Felipe; Salas, Cristian O.; Nazal, Mariajesus; Varela, Diego; Pérez-Castro, Ramón A.; Santibanez, Juan F.; Valdés-Valdés, Ricardo O.; Forero-Doria, Oscar; Echeverría, Javier (Frontiers in Pharmacology, 2022)
Background: There is abundant ethnopharmacological evidence the uses of these Solanum species as antitumor and anticancer agents. Here, we evaluate the antitumor activity of the So-lanum glycoalkaloid tomatine in hepatocellular carcinoma (HCC) in vitro and in vivo models. Purpose: To evaluate the anticancer effect of the Solanum glycoalkaloid tomatine in hepatocellular carcinoma (HCC) in vitro (HepG2 cells) and in vivo models. Methods: The resazurin reduction assay was performed to detect the effect of tomatine on cell viability in human HepG2 cell lines. Cellular apoptosis assays to detect programmed cell death using Annexin V. The expression of relative proteins was detected by Western blotting (WB). Reactive oxygen species (ROS) and calcium were detected by 2,7-Dichlorodihydrofluorescein diacetate and Fluo-4, respectively. Intrahepatic HepG2 xenograft mouse model was used to elucidate the effect of tomatine on tumor growth in vivo. Results and Discussion: Tomatine reduced HepG2 cell viability and induced the early apoptosis phase of cell death, consistently with caspase-3, -7, Bcl-2 family, and P53 proteins activation. Furthermore, tomatine increased intracellular ROS and cytosolic Ca+2 levels. Moreover, the NSG mouse xenograft model showed that treating mice with tomatine inhibited HepG2 tumor growth. Conclusion: Tomatine inhibits in vitro and in vivo HCC tumorigenesis in part via modulation of p53, Ca+2, and ROS signalling. Thus, the results suggest the potential cancer therapeutic use of tomatine in HCC patients.